ANALISIS PEGARUH PENYEDIAAN AIR BERSIH FASILITAS PEMERINTAH DAN MOTIVASI MASYARAKAT TERHADAP KESEJAHTERAAN MASYARAKAT BERPENGHASILAN RENDAH DI KABUPATEN LOMBOK BARAT - Balkis Ratu NL Esser (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
Providing clean water is an essential component a huge impact on health, the lives of rural people on low incomes in the district of West Lombok, good for daily necessities, household must meet health requirements, among others, free from germs, and does not contain toxic materials, therefore the water is one of the components to be utilized and developed in a focused, planned, as well as useful and can support life human being. A research development activities aimed to find out how the effect of water supply and motivation of the community, the facility will given by the government for low- income governments in western lombok district. In this thesis use non eksprimental ie with one taking data.Data obtained through non eksprimental method is, the data obtained as follows; of 46 people / respondents there were 37 people (63%), which felt the influence of procurement provision of facilities provided by the government.